FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN ANEMIA PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS MEURAXA BANDA - Kurniawati, Putri; Farida, Dewi; Efriana, Cut; Yanti, Putri; Sapira, Nurbela; Wati, Winda Fatma (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2023)
From the results of research in the work area of the Meuraxa Health Center, 435 pregnant women were obtained from January to December 2022, and pregnant women who experienced anemia were 11.15% of pregnant women. An initial survey conducted on December 12, 2022, found 5 respondents of pregnant women who experienced anemia in the working area of the Meuraxa Banda Aceh Health Center, of the 5 respondents, found 3 pregnant women who experienced anemia due to lack of knowledge of the importance of taking Fe tablets, and 2 respondents of pregnant women who experienced anemia due to low economic factors so that the need to meet nutritional status was difficult to meet. The purpose of the study was to determine the factors that influence the incidence of anemia in pregnant women in the working area of the Meuraxa Banda Aceh Health Center in 2023. This research method is analytical observational conducted on June 15, 2023 in the working area of the Meuraxa Banda Aceh Health Center with a population of 70 pregnant women. The research instrument is a questionnaire. Data analysis using univariate and bivariate analysis with the SPSS statistical program. The results of statistical tests with Chi Square obtained a p value = 0.000 (P <0.05) means that there is an influence between age and the incidence of anemia in pregnant women, the results of statistical tests with Chi Square obtained a p value = 0.008 (P <0.05) means that there is an influence between income and the incidence of anemia in pregnant women, the results of statistical tests with Chi Square obtained a p value = 0.000 (P < 0.05) means there is an influence between knowledge and the incidence of anemia in pregnant women, the results of statistical tests with Chi Square obtained a p value = 0.000 (P < 0.05) means there is an influence between consumption of Fe tablets with the incidence of anemia in pregnant women. The conclusion of this study is there is an influence of age, income, knowledge, consumption of Fe tablets with the incidence of anemia in pregnant women.